2019
DOI: 10.22481/el.v17i2.5345
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento de L2 e atrito de L1 em contexto dominante de L1: análise do VOT em Espanhol (L1) e Inglês (L2) (L2 development and L1 attrition in an L1-dominant environment: analysing voice onset time in L1 Spanish and L2 English)

Abstract: Neste estudo, investigamos a ocorrência de atrito de L1 entre aprendizes argentinos de inglês (L2) residentes em seu país de origem, o que constitui um ambiente dominante em L1. Analisamos a produção do VOT em plosivas iniciais de palavras em espanhol L1 de participantes monolíngües e bilíngües. Realizamos uma análise inferencial e uma verificação individual da produção de cada participante, que se mostrou complementar. Nossos resultados sugerem que não somente a L2 é afetada pela L1, mas também a L1 pode ser … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…Bilabial /p/ and dental /t/ VOT values, however, remained similar to those produced by monolingual English speakers. In addition, Alves et al (2019) found that the velar segment /k/ was realized with a semi-aspirated production even in monolingual speakers of Spanish, with a mean VOT value of /k/ of 46.61 ms. Therefore, it is possible that the compromised VOT productions of /k/ in L3 Spanish produced by the Polish HSs have been influenced by their L2 English; this is further evidence that the velar segment is first to present signs of attrition.…”
Section: Influence Of Hl/dl On L3 Votmentioning
confidence: 94%
“…Bilabial /p/ and dental /t/ VOT values, however, remained similar to those produced by monolingual English speakers. In addition, Alves et al (2019) found that the velar segment /k/ was realized with a semi-aspirated production even in monolingual speakers of Spanish, with a mean VOT value of /k/ of 46.61 ms. Therefore, it is possible that the compromised VOT productions of /k/ in L3 Spanish produced by the Polish HSs have been influenced by their L2 English; this is further evidence that the velar segment is first to present signs of attrition.…”
Section: Influence Of Hl/dl On L3 Votmentioning
confidence: 94%
“…There is a considerable number of studies in the L2 context that explore the circumstances and conditions under which regressive phonological and phonetic CLI from a person's L2 to their L1 takes place (see, e.g., Alves et al 2019;Barlow 2014;Chang 2012Chang , 2013Chang , 2019Cook 2003;Flege and Eefting 1987a;Jiang 2010;Kartushina et al 2016a;Lev-Ari and Peperkamp 2013;Lord 2008;Major 1992;Marx 2002;Mennen 2004;Sancier and Fowler 1997;Schereschewsky et al 2018;Stoehr et al 2017;Tobin et al 2017;Ulbrich and Ordin 2014;Waniek-Klimczak 2011). Most of these studies performed perceptual or acoustic analyses to deliver a quantitative assessment of L2 influence on L1 production, for instance, by comparing sequential bilinguals to a monolingual group or previously reported literature values (for a comprehensive literature review see Kartushina et al 2016b).…”
Section: Regressive CLI In L2 Studiesmentioning
confidence: 99%
“…On the other hand, it is less certain what factors have to be present in order for regressive CLI to occur in non-immersive or typical classroom learning contexts where exposure is more restricted, as is the case for the learners in the present study. Still, research conducted in instructed learning contexts and L1-dominant speaking environments (e.g., Eefting 1987a, 1987b;Kartushina et al 2016a;Lord 2008;Alves et al 2019;Herd et al 2015;Kupske 2016;Schereschewsky et al 2018;Waniek-Klimczak 2011) has uncovered a number of interesting observations and tendencies.…”
Section: Regressive CLI In L2 Studiesmentioning
confidence: 99%
See 1 more Smart Citation